Fish genetics and aquaculture biotechnology. - Pandian, T.J., C.A. Strussmann, M.P. Marian (Editors) (Science Publishers, 2005)
Some papers were presented at the International Conference on "Advanced Technologies in Fisheries and Marine Sciences".Includes bibliographical references and index.